PENERAPAN KETERAMPILAN SAINS UNTUK MENINGKATKAN HASIL BELAJAR FISIKA SISWA KELAS XI IPA 2 SMA NEGERI 1 RAMBAH - Ali Pullaila (STKIP ROKANIA, 2019)
The purpose of this study is to describe the learning outcomes of students who are taught using the science process skills approach to the subject matter of temperature and heat. This study included Classroom Action Research (PTK) by applying the science process skills approach as an alternative action to improve physics learning outcomes of students of class XI-IPA2 in SMA 1 Rambah the 2018/2019 school year in the subject matter of temperature and heat. The results showed that the learning outcomes of students taught by using the science process skills approach to the subject matter of temperature and heat were likely to increase. In the first cycle obtained a maximum value of 80 and a minimum value of 10 with an average of 48.87 with a standard deviation of 19.49. Then in the second cycle the maximum value was 80 and the minimum value was 20 with an average of 63.37 and the standard deviation of 15.11 and the third cycle obtained a minimum value of 40 and a maximum value of 90 with an average of 75.13 and a standard deviation of 13 , 84. The conclusion in this study is that there is an increase in science learning outcomes in improving physics learning outcomes of students of class XI Science 2 SMA 1 Rambah.